2017
DOI: 10.1112/s0010437x1700762x
|View full text |Cite
|
Sign up to set email alerts
|

The Kodaira dimension of complex hyperbolic manifolds with cusps

Abstract: We prove a bound relating the volume of a curve near a cusp in a complex ball quotient X = B/Γ to its multiplicity at the cusp. There are a number of consequences: we show that for an n-dimensional toroidal compactification X with boundary D, K X +(1−λ)D is ample for λ ∈ (0, (n + 1)/2π), and in particular that K X is ample for n 6. By an independent algebraic argument, we prove that every ball quotient of dimension n 4 is of general type, and conclude that the phenomenon famously exhibited by Hirzebruch in dim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Combining (6.2) with (5.3) and (6.7), we finally obtain the lower bound (1.1) on vol(E GG k,• Ω X ), which proves Theorem 1.1. The expression (1.1) being valid for any k, we can use the results of [3] to determine an order k after which the algebra E GG k,• Ω X has maximal growth. For example, it is not hard to obtain an asymptotic expansion of (1.1), with leading coefficient…”
Section: Uniform Lower Bound In K On Vol(e Gg Km ω X )mentioning
confidence: 99%
See 1 more Smart Citation
“…Combining (6.2) with (5.3) and (6.7), we finally obtain the lower bound (1.1) on vol(E GG k,• Ω X ), which proves Theorem 1.1. The expression (1.1) being valid for any k, we can use the results of [3] to determine an order k after which the algebra E GG k,• Ω X has maximal growth. For example, it is not hard to obtain an asymptotic expansion of (1.1), with leading coefficient…”
Section: Uniform Lower Bound In K On Vol(e Gg Km ω X )mentioning
confidence: 99%
“…Using the results of [3], it is not hard to derive explicit orders k for E GG k,• Ω X to have maximal growth:…”
Section: Introductionmentioning
confidence: 99%
“…We also expect Theorem C to be true uniformly in X(1), and that the same idea for the proof should work with some modifications. The methods investigated here apply more generally to rank one lattices (see [BT15] for an application to complex ball quotients), and we expect the torsion conjecture in the case of abelian varieties parametrized by a rank one Shimura variety to be proven similarly.…”
mentioning
confidence: 94%
“…The noncompact manifold X admits toroidal compactification X by [1] in case Γ is arithmetic and by [12] for non-arithmetic Γ. It is shown that X possesses many hyperbolic properties (see for example, [5], [6], [7], [16]).…”
Section: Introductionmentioning
confidence: 99%
“…From our point of view, the proof boils down to the construction of holomorphic symmetric differentials vanishing at infinity, which can also be thought of as a generalization of cusps form in modular curves. As inspired by the works of Mumford [14], Nadel [15] and Bakker-Tsimerman [5], an important element for the existence of the desired symmetric differentials is to make sure the size of the lattice "Γ is sufficiently small" or the infinity "D is not too big". Hence we introduce the notion of canonical radius of a cusp, which measures the size of the infinity corresponding to a cusp of Γ.…”
Section: Introductionmentioning
confidence: 99%